Pengaruh Kompensasi, Lingkungan Kerja Dan Komunikasi Terhadap Kepuasan Kerja Pegawai (Studi Pada Pegawai Dinas Koperasi Usaha Mikro dan Perdagangan di Kota Batu) - Eva Sulistiana; Abdul Kodir Djaelani; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of Compensation, Work Environment, and Communication, on Employee Job Satisfaction. The research used is descriptive quantitative method. The population in this study were 116 employers of Cooperative Official in Batu City. While the sample used in this study was purposive sampling with proportionate stratified random sampling using the Slovin formula so that there were 54 samples. The data used are secondary data and primary data using a questionnaire technique. The data analysis method used is instrument test: validity and reliability test, normality test, classical assumption test: multicollinearity test and heteroscedasticity test, multiple linear regression analysis, hypothesis testing: simultaneous test, partial test and coefficient of determination. From the results of the study simultaneously obtained the results that Compensation, Work Environment, and Communication have a significant effect on Employee Job Satisfaction. Partially the result that Compensation have a significant effect on Employee Job Satisfaction, Work Environment do not Have Significant effect on Employee Job Satisfaction, Communication have a significant effect on Employee Job Satisfaction. Keywords: Compensation, Work Environment, Communication, Job Satisfaction.